2007
DOI: 10.1177/0003319707299205
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Positron Emission Tomography With (18)F-Fluorodeoxyglucose for the Diagnosis of Vascular Graft Infection

Abstract: Vascular graft infection is associated with a high morbidity and mortality rate. Diagnosis is difficult, as there is no single diagnostic criterion that has a 100% accuracy. A combination of physical examination, laboratory tests, and several imaging techniques is mandatory. Beside a wide range of indications in the oncological field, positron emission tomography with (18)F-fluorodeoxyglucose (FDG-PET) has a well-known role in the diagnosis of bone and soft-tissue infections. Some authors have recently reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 11 publications
0
21
0
1
Order By: Relevance
“…In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ).…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of recent manipulations, 1,[33][34][35] Several studies have reported that PET/CT is useful for the diagnosis of intra-abdominal VGI. 1,[28][29][30][31][32][42][43][44][45][46] Three recent studies summarized the role of PET/CT for the diagnosis of VGI. [30][31][32] Although there were variables in imaging techniques and patient selection among these studies and other studies, the sensitivity and specificity of PET/CT were similar to those reported with standard CT for the diagnosis of VGI [28][29][30][31][32]39,[43][44][45][46] (Table 1 1 ).…”
Section: Intra-abdominal Vgimentioning
confidence: 99%
“…[28][29][30][31][32][43][44][45][46] On the basis of the published studies, it is reasonable to use standard CT as the initial imaging modality for the diagnosis of VGI.…”
mentioning
confidence: 99%
“…18 F-FDG PET is widely used for the assessment of cancer. Given the high metabolic activity of inflammatory cells, 18 F-FDG is also a useful marker for various active infectious and inflammatory processes (11)(12)(13), including reports of a high sensitivity in the diagnosis of vascular prosthetic infections (14,15). Hybrid 18 F-FDG PET/CT has established the role of 18 F-FDG imaging for the assessment of suspected vascular graft infection, providing accurate anatomic localization of the site of infection with subsequent improved specificity (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The accuracy was satisfactory in case of an AUC > 0. 8. Results The feature selection process yielded the textural features named variance (AUC = 0.88), high grey level zone emphasis (AUC = 0.87), small zone low grey level emphasis (AUC = 0.80), and small zone high grey level emphasis (AUC = 0.81) most optimal for distinguishing between groups I and II.…”
Section: Ffluorodeoxyglucose (mentioning
confidence: 99%
“…Non-invasive 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) imaging may play an important role in increasing the diagnostic accuracy of infectious diseases with inherent elevated intracellular glucose metabolism [6][7][8][9][10][11]. The PET images can either be evaluated semi-quantitatively using the maximal standardized uptake value (SUVmax) and the tissue-tobackground ratio (TBR), and visually using the visual grading scale (VGS).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%